2017
DOI: 10.18632/oncotarget.18331
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide 5-hydroxymethylcytosine patterns in human spermatogenesis are associated with semen quality

Abstract: We performed immunofluorescent analysis of DNA hydroxymethylation and methylation in human testicular spermatogenic cells from azoospermic patients and ejaculated spermatozoa from sperm donors and patients from infertile couples. In contrast to methylation which was present throughout spermatogenesis, hydroxymethylation was either high or almost undetectable in both spermatogenic cells and ejaculated spermatozoa. On testicular cytogenetic preparations, 5-hydroxymethylcytosine was undetectable in mitotic and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…In neither chromosome did we observe DNA hemimethylation, partial methylation, or absence of 5mC. Overall, this 5mC pattern was very similar to that reported previously in human chorion, lymphocytes, and spermatogonia [Kokalj-Vokac et al, 1998;Pfarr et al, 2005;Pendina et al, 2005;Efimova et al, 2017].…”
Section: Efimova Et Alsupporting
confidence: 90%
“…In neither chromosome did we observe DNA hemimethylation, partial methylation, or absence of 5mC. Overall, this 5mC pattern was very similar to that reported previously in human chorion, lymphocytes, and spermatogonia [Kokalj-Vokac et al, 1998;Pfarr et al, 2005;Pendina et al, 2005;Efimova et al, 2017].…”
Section: Efimova Et Alsupporting
confidence: 90%
“…low sperm concentration (Marques et al, 2008 ; Poplinski et al, 2010 ). More recently, it was also reported that modification in 5hmC pattern in sperm is associated with male infertility (Wang et al, 2015 ; Efimova et al, 2017 ). In these reports, infertile males were shown to contain higher rate of 5 hmC than fertile males and infertility correlated with defects in sperm morphology and a high sperm DNA fragmentation rate (Efimova et al, 2017 ).…”
Section: Dna Methylation and Beyondmentioning
confidence: 95%
“…More recently, it was also reported that modification in 5hmC pattern in sperm is associated with male infertility (Wang et al, 2015 ; Efimova et al, 2017 ). In these reports, infertile males were shown to contain higher rate of 5 hmC than fertile males and infertility correlated with defects in sperm morphology and a high sperm DNA fragmentation rate (Efimova et al, 2017 ). Several studies have also reported that a link exists between assisted reproductive technologies (ART) and loss of imprinting resulting in an increased incidence of genomic imprinting disorders in children conceived via ART (for review, see Ventura-Juncá et al, 2015 ).…”
Section: Dna Methylation and Beyondmentioning
confidence: 95%
“…Interestingly, the 5hmC levels on the gene bodies and proximal promoters of highly expressed genes were markedly higher than those of genes expressed at lower levels in different stages of mouse spermatogenesis, indicating that 5hmC plays an important role in active gene transcription in spermatogenesis (Gan et al., ). Alteration in 5hmc has been found to exist widely in globozoospermia spermatozoa (Wang et al., ) and the spermatozoa from infertile men (Efimova et al., ). We recently reported the presence of genome‐wide alteration of 5hmc in the spermatozoa from the men exposed to bisphenol A (BPA; Zheng et al., ), a widely studied endocrine‐disrupting chemical (EDC) which has a power to reduce human sperm quality, according to the human epidemiologic studies (Li et al., ).…”
Section: Introductionmentioning
confidence: 99%